1993
DOI: 10.1128/mcb.13.8.5070
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of a yeast SH3 protein leads to conditional viability with defects in cytoskeletal and budding patterns.

Abstract: Mutations in genes necessary for survival in stationary phase were isolated to understand the ability of wild-type Saccharomyces cerevisiae to remain viable during prolonged periods of nutritional deprivation. Here we report results concerning one of these mutants, rvsl67, which shows reduced viability and abnormal cell morphology upon carbon and nitrogen starvation. The mutant exhibits the same response when cells are grown in high salt concentrations and other unfavorable growth conditions. The RVS167 gene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
235
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(246 citation statements)
references
References 81 publications
10
235
1
Order By: Relevance
“…The N and C-terminal regions of Bin1 are related to amphiphysin, a neuronal protein that is a paraneoplastic autoimmune antigen in breast and lung cancer (David et al, 1994;Dropcho, 1996). The same regions are also related to Rvs167 and Rvs161, two negative regulators of the cell cycle in yeast (Crouzet et al, 1991;Bauer et al, 1993) [Bin1 is related but not homologous since it cannot complement Rvs functions (Sakamuro et al, 1996)]. Amphiphysin and brainspeci®c splice forms of Bin1, also termed amphiphysin II or amphiphysin isoform, have been implicated in receptor-mediated endocytosis (David et al, 1996;Wigge et al, 1997;Owen et al, 1998).…”
Section: Role Of Interaction With the Cell Fate Adaptor Protein Bin1mentioning
confidence: 99%
“…The N and C-terminal regions of Bin1 are related to amphiphysin, a neuronal protein that is a paraneoplastic autoimmune antigen in breast and lung cancer (David et al, 1994;Dropcho, 1996). The same regions are also related to Rvs167 and Rvs161, two negative regulators of the cell cycle in yeast (Crouzet et al, 1991;Bauer et al, 1993) [Bin1 is related but not homologous since it cannot complement Rvs functions (Sakamuro et al, 1996)]. Amphiphysin and brainspeci®c splice forms of Bin1, also termed amphiphysin II or amphiphysin isoform, have been implicated in receptor-mediated endocytosis (David et al, 1996;Wigge et al, 1997;Owen et al, 1998).…”
Section: Role Of Interaction With the Cell Fate Adaptor Protein Bin1mentioning
confidence: 99%
“…First, Bin1 inhibits cell transformation by Myc or adenovirus E1A . Second, Bin1 is related to RVS167, a negative regulator of the cell cycle in yeast (Bauer et al, 1993). Third, although widely expressed in normal cells, Bin1 is poorly expressed or undetectable in *50% of carcinoma cell lines and primary breast carcinomas examined .…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrate actin-associated proteins containing SH3 domains include proteins with structural roles such as fodrin and nebulin (Merilainen et al, 1993;Wang et al, 1996), unconventional myosins (Bement et al, 1994;Stoffler et al, 1995;Goodson et al, 1996), kinases and associated molecules (Flynn et al, 1993;Turner and Miller, 1994;Hildebrand et al, 1996), and other actin-binding proteins such as cortactin (Wu and Parsons, 1993). In S. cerevisiae, SH3-containing proteins include the actin-associated proteins Abplp (Drubin et al, 1990), Slalp (Holtzman et al, 1993), and Rvs167p (Bauer et al, 1993), as well as Bemlp and the recently identified Boilp and Boi2p, which have roles in the maintenance of normal cellular and cytoskeletal morphology (Chenevert et al, 1992;Bender et al, 1996;Matsui et al, 1996). A number of yeast proteins implicated in cytoskeletal function, including Abplp, Slalp, Boilp, Boi2p, and Srv2p (Field et al, 1990), contain proline-rich regions which include amino acid sequences similar to known binding sites for SH3 domains.…”
Section: Introductionmentioning
confidence: 99%
“…Like Abplp and Srv2p, Slalp (synthetic lethal-ABP1), Sla2p, and Sac6p (yeast fimbrin) coimmunolocalize in the cortical actin cytoskeleton (Drubin et al, 1988;Adams et al, 1989; Lila, Yang, and Drubin, unpublished observations) and were identified in a screen for strong genetic enhancers of an ABP1 null mutation (synthetic lethals; Holtzman et al, 1993). Rvsl67p interacts with actin in the yeast two-hybrid system (Amberg et al, 1995), and has functions important for sporulation and viability under adverse growth conditions (Bauer et al, 1993). Rvs167p and Slalp also contain one and three SH3 domains, respectively, suggesting that they too may interact physically with other cytoskeletally associated proteins.…”
Section: Introductionmentioning
confidence: 99%